DEVELOPMENT OF ICT TRACK CHANGE FEATURE IN DIGITAL EDITING COURSES TO IMPROVE THE COMPETENCE OF PROSPECTIVE TEACHER STUDENTS - Restu Bias Primandhika; Aurelia Sakti Yani (Kopertis Region IV Jabar and Banten, 2022)
This study aims to develop an evaluation tool for reading comprehension tests based on TPACK (Technological Pedagogical Content Knowledge) using the Track Change feature. The resulting evaluation tool is expected to be a reference for teachers in assessing reading comprehension skills. The testmoz application is relevant software in the form of a test tool, the application will assist teachers in carrying out direct assessments in providing online assessments to students. The research approach used is a qualitative research approach of the type of development (Research and Development). The data was collected through a literature study, the design of a reading comprehension assessment tool model using testmoz, and the results of testing the use of the product. Data collection techniques in the form of expert validation and product trial results. The research output is in the form of scientific articles to be published in national journals and products in the form of an evaluation tool for reading comprehension tests using the testmoz application, as well as additional outputs of 1 IPR product from research results. TKT measured is the level 2.